THE EFFECT OF SERVICE, PRICE, QUALITY, AND BRAND ON CUSTOMER SATISFACTION IN PT. SARANA BAJA PERKASA - Vivian Limwin; Felix; Rosinta Romauli Situmeang; Auril (Mount Hope Economic Global Journal, 2024)
Customer satisfaction is one of the determining factors for the development of a company. Therefore, the aim of this research is to find out whether there is an influence of service, price, quality, and brand on customer satisfaction at PT. Mighty Steel Facilities. The research method is quantitative with a descriptive approach. The population of this study were all visitors to PT. Mighty Steel Facilities. The sample determination method in this study used simple random sampling, which had a sample size of 70 after adjusting to the specified criteria. Data was collected using a questionnaire which was then analyzed using the SPSS 24 application. The data analysis technique involved testing classical assumptions, coefficient of determination and hypothesis testing. The research results show that simultaneously the service, price, quality and brand variables influence customer satisfaction. Partially, the service and quality variables have a positive and significant effect on customer satisfaction, while the price and brand variables do not affect customer satisfaction at PT. Mighty Steel Facilities. The overall influence of the independent variables on customer satisfaction is 50.4%. Keywords: Service, price, quality, brand. Customer satisfaction.